2007
DOI: 10.1210/me.2006-0356
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Coordination of Hepatic Glucose Metabolism by the 6-Phosphofructo-2-Kinase/Fructose-2,6- Bisphosphatase:Glucokinase Complex

Abstract: Glucokinase (GK) and 6-phosphofructo-2-kinase (PFK-2)/fructose-2,6-bisphosphatase (FBP-2) are each powerful regulators of hepatic carbohydrate metabolism that have been reported to influence each other's expression, activities, and cellular location. Here we present the first physical evidence for saturable and reversible binding of GK to the FBP-2 domain of PFK-2/FBP-2 in a 1:1 stoichiometric complex. We confirmed complex formation and stoichiometry by independent methods including affinity resin pull-down as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Consistent with this hypothesis, we demonstrated in this study that ectopic expression of PFKFB3 in the nucleus did not have a significant effect on total cell glycolysis but rather stimulated cellular proliferation. We should emphasize, however, that our findings should not be interpreted as an argument against the well established role for Fru-2,6-BP in the regulation of glycolysis (43,(45)(46)(47)(48)(49)(50). We suspect that Fru-2,6-BP may be primarily involved in the regulation of glycolysis in normal non-proliferating cells such as neurons and hepatocytes, whereas, in transformed cells, Fru-2,6-BP may serve a dual function in glycolysis and cell cycle regulation.…”
Section: Discussionmentioning
confidence: 54%
“…Consistent with this hypothesis, we demonstrated in this study that ectopic expression of PFKFB3 in the nucleus did not have a significant effect on total cell glycolysis but rather stimulated cellular proliferation. We should emphasize, however, that our findings should not be interpreted as an argument against the well established role for Fru-2,6-BP in the regulation of glycolysis (43,(45)(46)(47)(48)(49)(50). We suspect that Fru-2,6-BP may be primarily involved in the regulation of glycolysis in normal non-proliferating cells such as neurons and hepatocytes, whereas, in transformed cells, Fru-2,6-BP may serve a dual function in glycolysis and cell cycle regulation.…”
Section: Discussionmentioning
confidence: 54%
“…To investigate the function of TIGAR at the outer mitochondrial membrane, we considered previous studies that identified the binding between the bisphosphatase domain of PFK2/ FBPase and glucokinase (27)(28)(29), a member of the HK family expressed mainly in the liver, pancreas, gut, and brain (5). Because TIGAR resembles the bisphosphatase domain of PFK2/ FBPase (16,17), we reasoned that TIGAR might form a complex with HK family members.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that binding to PFK2/FBPase enhances the activity of glucokinase (27,31,32), and so we examined the effect of TIGAR on HK activity under normoxic and hypoxic conditions. Although HK2 depletion by siRNA strongly reduced HK activity in both conditions, a clear reduction in HK activity was also seen after siRNA depletion of TIGAR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A tentative hypothesis is that, in the absence of phosphorylation of Ser-32, glucokinase can bind to PFK2 and facilitate formation of fructose-2,6-P 2 through either inhibition of the bisphosphatase, because glucokinase binds to the bisphosphatase domain (8), or channelling involving phosphoglucoisomerase. A further possibility is that glucokinase may increase the kinase activity of PFK2 as suggested from a study on liver homogenates (38). The higher cell content of fructose-2,6-P 2 with titrated glucokinase overexpression in hepatocytes from fa/fa compared with Fa/?…”
Section: Discussionmentioning
confidence: 98%